Sistem Informasi Geografis Berbasis Web untuk Pemetaan Sebaran Alumni Menggunakan Metode K-Means - Handoko, Slamet; Sediono, Eko; Suhartono, Suhartono (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
The  graduates  of  State  Polytechnic  of  Semarang  are  not  only  the  member  of  social  community  but  also part  of  State Polytechnic  of Semarang  community  who  have  academic  knowledge  and  special  skills.  Based  on  the  researcher  observation  the  graduates  of  State Polytechnic  of  Semarang  are  not  recorded,  the  management  of  State  Polytechnic  of  Semarang  has  not  provided  a  system  that  can facilitate  the  interaction  between  State  Polytechnic  of  Semarang  and  graduates.  In  this  thesis,  the  system  for  mapping  the  graduates distribution is aimed to measure the level of the  graduates  compliance skill with the competence area of their job. The method of KMeans Clustering is used for grouping the distribution of State Polytechnic of Semarang graduates. Grouping or clustering mechanism in this system is based on four variables. They are  type of company, job classification, working area, and competency of study program. While  the geographical position of graduates is used to filter the data when the users are searching the graduates location in a ce rtain province.  In  this  research  the  cluster  is  divided  into  three,  they  are,  cluster  one:  graduates  have  matching  competence,  cluster  two: graduates have matching enough competence, and cluster three: graduates have no matching competence.Keywords: Clustering;  GIS ;  K-Means